2016
DOI: 10.2147/oarrr.s123549
|View full text |Cite
|
Sign up to set email alerts
|

Systemic lupus erythematosus and pulmonary arterial hypertension: links, risks, and management strategies

Abstract: Systemic lupus erythematosus (SLE) is characterized by the second highest prevalence of pulmonary arterial hypertension (PAH), after systemic sclerosis, among the connective tissue diseases. SLE-associated PAH is hemodynamically defined by increased mean pulmonary artery pressure at rest (≥25 mmHg) with normal pulmonary capillary wedge pressure (≤15 mmHg) and increased pulmonary vascular resistance. Estimated prevalence ranges from 0.5% to 17.5% depending on the diagnostic method used and the threshold of righ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
78
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(79 citation statements)
references
References 57 publications
(85 reference statements)
1
78
0
Order By: Relevance
“…Several researchers presented that disease duration, Raynaud's phenomenon, pleuritis, positive anti-U1RNP antibody, positive anti-SSA antibody, and positive anti-cardiolipin antibodies are independent predictors of PH in SLE. 15,21 We found that tachypnea, which has been rarely investigated, is an important marker relevant to PH in SLE. Dyspnea is one of the cardinal clinical manifestations of PH.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Several researchers presented that disease duration, Raynaud's phenomenon, pleuritis, positive anti-U1RNP antibody, positive anti-SSA antibody, and positive anti-cardiolipin antibodies are independent predictors of PH in SLE. 15,21 We found that tachypnea, which has been rarely investigated, is an important marker relevant to PH in SLE. Dyspnea is one of the cardinal clinical manifestations of PH.…”
Section: Discussionmentioning
confidence: 88%
“…Consistent with findings in previous reports, increased positive percentages of serositis and Raynaud's phenomenon concurrent with extended illness duration and increased SDI score in PH group were observed in our study. 20,21 Multiple organs were injured during the course of SLE progression. Thus, increased pulmonary vascular resistance (PVR) plays an important role in PH development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there is little to suggest that treatments targeting ILD have any ameliorating effect on PAH. 116 Nonetheless, there is clear evidence in support of PAH-specific therapies to lessen symptom burden and reduce clinically meaningful events, such as hospitalization (risk reduction, 57%). 117 Hospitalization represents a major risk in patients with group 1 PAH, 118 and combination PAH-specific therapy reduced all-cause hospitalization from 15% to 5% compared with single-drug treatment regimens.…”
Section: Ph In Ctdmentioning
confidence: 99%
“…In an analysis on a Chinese cohort, pleurisy was an independent predictive factor of PAH in lupus . The (2) antibodies specific to the antiphospholipid PAH . The treatment should be promptly (3) initiated in order to increase survival.…”
Section: Clinical Casesmentioning
confidence: 99%